THE EFFECTIVENESS OF MANAGEMENT BY OBJECTIVE (MBO) IN BUSINESS ORGANIZATIONS - Islam Djumaniyazov; Prof.Dr. Victor Randall (Scholar Express Journals, 2022)
Management by objectives acts as the major tool of action for the performance analysis of the organization requirement of the employees in any range of business environment. From the inception stage of employee in the organization they need to calculate and measures the performance reviews with a knowledge and learning aspects of the national bank of Uzbekistan. The study focuses on the national banking system of the employee’s performance, and the standards of the work orientation in the organization. MBO has been used in Organization more than last four decades since it was introduced by Drucker in 1954. According to Bush’s (1998) research bout 60 per cent of the respondents indicated that they use MBO in their organizations. In Norway MBO is probably is most widespread short-term planning system. MBO is a tool that felt into disuse because its requirements do not fit in today’s entrepreneurial culture. Regarding to different researchers, productivity and performance efficiency has been increased after the introduction of MBO and they found out that the impact of MBO was substantially greater where top-management commitment was high. All the departments of the organization need to involve in the study for the accurate rate of results and the implications of the knowledge activities in the learning environment of the business perspectives, and to reach the goal of the organization. The study also focuses on the presentations skills and the data analysis aspects of the different age groups, and deterministic levels of the management in the organization. It also covers the information from the banking sectors of the individualistic performance reviews, and the compensation benefits towards the growth of the organization and its improvement towards the business environment.
Keywords: Management; MBO